Strengthening of international exchange of information to combat tax fraud on income tax: comparative case study between Ecuador and Chile - Velasco Mancheno, Consuelo (2018)
Tax evasion on income tax affects not only public revenues but also it affects the trust in public finance. For that reason, international public finance experts and organizations have boosted the cooperation between national tax authorities, specially, though a mechanism called “exchange of information”, which is based on two international standards: Exchange of information on request and automatic exchange of information. Tax evasion on the income tax affects not only public revenues, but also confidence in public finances. For this reason, experts and international organizations related to this issue have fostered cooperation among national tax authorities, especially through a mechanism called "information exchange" based on two international standards: exchange of information on request and automatic exchange of information. This article, in its first part, will analyze the meaning of tax fraud on income tax and its characteristics and what is the international exchange of tax information. In the second part, there will be a comparative analysis of the application of this mechanism in Chile and Ecuador. Finally, the conclusions of the study and the recommendations for the strengthening of the exchange of tax information in Ecuador will be presented.